Missiology as Global Conversation: The UCA Mission Programme - Kim, Kirsteen (International review of mission, 2004)
The United College of the Ascension (UCA) is continuing the tradition of Selly Oak, Birmingham, UK, where UCA is situated and where mission education and training has been taking place in an ecumenical setting since 1912. The college, which is sponsored by the United Society for the Propagation of the Gospel (Anglican) and the Methodist Church of Great Britain, works in close cooperation with the University of Birmingham, and particularly its Centre for Missiology and World Christianity. The UCA Mission Programme (UCAMP) is an imaginative and flexible programme of mission preparation, reflection and exposure for people crossing boundaries in mission in different directions. Such people include the missionaries and mission partners of a number of different organizations, clergy on sabbatical, those called from overseas to ministry and mission in the UK, and scholarship holders and visiting fellows invited as a result of partnership links with churches worldwide. Utilizing the varied mission experiences participants represent, and the international nature of the college community, mission studied at UCA have evolved to become a global conversation of (contextual) theologies. UCAMP is structured around a core course of biblical and theological studies, the history of mission, cross-cultural communications, social and global studies, and religious studies. UCAMP also includes personal and professional development, and the opportunity to tailor programmes to vocational and personal interest by drawing on the rich resources of UCA, Selly Oak and the multi-cultural city of Birmingham. UCAMP provides an up-to-date model of mission education and training for the 21st century.